Stabilization of the Monetary and Financial Market as a Necessary Condition for the Transition to Sustainable Development - Glazyev, Sergey Yurievich (Economy of Regions, 2016)
In the absence of the effective system of state regulation, the monetary and financial market not only does not carry out the function of the financing of value-adding investment, but it is also a source of destabilization of the Russian economy. In the article, the analysis of the policy instruments of the Central Bank of the Russian Federation is provided. The reasons and consequences of the financial and currency speculation and transition to free ruble exchange rate are considered. The concept of «inflation targeting» is investigated and the conclusion that the transition to the inflation targeting declared by the Central Bank of Russia did not achieve the stated goals is drawn. The need for using the instruments as the control parameters, corresponding to a host of factors of currency system instead of using only refinancing rate is reasoned. The arguments to apply the currency restrictions are considered. The assessment of a current situation of the Russian monetary and financial system is given as uncontrollable. The manipulation of the Russian monetary and financial market from the foreign financial institutions connected with issuers of world currencies is identified as the main political consequence of the currency and monetary policy. The aggravation of stagflation and of crisis phenomena in the Russian economy at the further realization of similar monetary policy is forecasted. In the article, a number of measures for stabilization of the Russian economy by the state regulation of the monetary and credit sphere, which would secure the monetary and financial market against external and internal threats, is offered.